Wedlock - Ḥijāzī, Sayyid Rūḥ Allāh, 1979 or 1980-; Davari, Mehdi; Talebabadi, Ali (Academic Video Online, 2013)
The Mahmoodis live in an old large house, having traditional values and beliefs. They have decided to renovate the building. Mrs Mahmoodi's niece arrives with her architect husband to take care of the renovation. Conflicts about renovating the house expand to their relations and connections. It is gradually revealed that the people in the house are torn between traditional and modern viewpoints and so are the guests.